FORMULA OPTIMIZATION AND IN VITRO RELEASE KINETIC STUDIES OF DILTIAZEM HYDROCHLORIDE MUCOADHESIVE BILAYER BUCCAL FILM - WINARTI, LINA; LAILY, AFALAH ZULFA; SARI, LUSIA OKTORA RUMA KUMALA; IRAWAN, EKA DEDDY; NURRAHMANTO, DWI; ROSYIDI, VIDDY AGUSTIAN; BARIKAH, KUNI ZUAIMAH; AMELIANA, LIDYA (International Journal of Applied Pharmaceutics, 2021)
Objective: This research aims to determine the amount of hydroxypropyl methylcellulose (HPMC) and chitosan, which can produce the optimum buccal film formula and to determine the release kinetics of diltiazem hydrochloride in vitro. Methods: The film was prepared by the solvent casting method. The formula's optimization was carried out using factorial design, which was processed using Design Expert 11.0.0 software, while the release kinetics was analyzed using the DDSolver program. Results: The optimization results show that HPMC and chitosan (30 mg: 10 mg) is the amount of polymer that can produce the optimum formula. The buccal film formula has a swelling index of 2.92, a mucoadhesive strength of 64.40 gF, and a mucoadhesive residence time of 464 min. In vitro release study showed 97.64% release of Diltiazem hydrochloride after 480 min. The release kinetic’s of diltiazem hydrochloride follow the Korsmeyer Peppas model. Conclusion: Thus, it can be concluded that the prepared formulation of the buccal mucoadhesive film can be a delivery system for diltiazem hydrochloride.